2018
DOI: 10.1186/s12938-018-0472-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MR thermometry based on phase-drift correction PRF shift method at 0.35 T

Abstract: BackgroundNoninvasive magnetic resonance thermometry (MRT) at low-field using proton resonance frequency shift (PRFS) is a promising technique for monitoring ablation temperature, since low-field MR scanners with open-configuration are more suitable for interventional procedures than closed systems. In this study, phase-drift correction PRFS with first-order polynomial fitting method was proposed to investigate the feasibility and accuracy of quantitative MR thermography during hyperthermia procedures in a 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Field drifts are most likely responsible for consistent underestimation of lesion sizes listed in Table 1. This phenomenon has been widely reported on in the literature [12,[29][30][31][32] and several methods have been proposed to mitigate it for improved accuracy of PRFS [33,34]. Real-time corrections for field drifts at the ablation site are currently being investigated by our group.…”
Section: Tablementioning
confidence: 87%
“…Field drifts are most likely responsible for consistent underestimation of lesion sizes listed in Table 1. This phenomenon has been widely reported on in the literature [12,[29][30][31][32] and several methods have been proposed to mitigate it for improved accuracy of PRFS [33,34]. Real-time corrections for field drifts at the ablation site are currently being investigated by our group.…”
Section: Tablementioning
confidence: 87%
“…Open-configuration MR scanners are characterized by lower fields (<1 T) and also involve a lower purchase price and reduced operational cost compared with high-field instruments. Therefore, Chen et al showed by in vitro experiments with phantoms and porcine liver that MRT based on drift-correction phase PRFS with first-order polynomial fitting can be applied to monitor temperature changes during MW ablation in a low-field (0.35 T) configuration whole-body MR scanner designed for applications in humans (Chen et al, 2018). However, work on high-field PRFS (cited above) consistently indicated that discrepancies between PRFS and fiber optic probe-measured temperatures are on the order of %1 C, whereas errors may increase to about 2 C for fields as low as 0.35 T (Chen et al, 2018).…”
Section: Destroying Tissue By Heating With Ultrasound: Mrt Applications In Tissue Ablationmentioning
confidence: 99%
“…Therefore, Chen et al showed by in vitro experiments with phantoms and porcine liver that MRT based on drift-correction phase PRFS with first-order polynomial fitting can be applied to monitor temperature changes during MW ablation in a low-field (0.35 T) configuration whole-body MR scanner designed for applications in humans (Chen et al, 2018). However, work on high-field PRFS (cited above) consistently indicated that discrepancies between PRFS and fiber optic probe-measured temperatures are on the order of %1 C, whereas errors may increase to about 2 C for fields as low as 0.35 T (Chen et al, 2018). Phase PRFS tests in vivo on volunteers showed that drift correction had a marked effect on the stability of temperature measurements in the human brain, setting the stage for future clinical tests involving MW hyperthermia.…”
Section: Destroying Tissue By Heating With Ultrasound: Mrt Applications In Tissue Ablationmentioning
confidence: 99%
“…For several thermometry studies, magnetic resonance (MR)-based analysis (spectroscopy and imaging) is a valuable analytical tool among other things for biological objects. [1][2][3] Furthermore, knowledge of in vivo temperature changes is important in clinical diagnostic, therapy (such as hypothermia [4,5] or hyperthermia [6] ) or investigation of implants distortions. [7] Conventional thermometers cannot be used for temperature measurements in strong magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…Whether solids, liquids or gases, knowledge of the local temperature or the temperature distribution can lead to the optimization of processes and structures or improve the diagnosis and therapy of diseases (theranostics). For several thermometry studies, magnetic resonance (MR)‐based analysis (spectroscopy and imaging) is a valuable analytical tool among other things for biological objects [1–3] . Furthermore, knowledge of in vivo temperature changes is important in clinical diagnostic, therapy (such as hypothermia [4,5] or hyperthermia [6] ) or investigation of implants distortions [7] .…”
Section: Introductionmentioning
confidence: 99%